Urbanization and Urban-Rural Inequality in China: A New Perspective from the Government's Development Strategy - Lin, Justin Yifu (2012)
This paper offers a novel explanation for the lower urbanization rate and great urban-rural inequality in China. Our study reveals that, heavy-industry-oriented development strategy will result in lower urbanization rate and higher urban-rural inequality. The greater the degree of heavy-industry-oriented development strategy is, the lower the urbanization rate is, and the higher the urban-rural inequality is. From a dynamic perspective, heavy-industry-oriented development strategy reduces the capital accumulation rate, which results in a slower progress of urbanization and a highly persistent urban-rural inequality. The higher the degree of heavy-industry-oriented development strategy, the slower the progress of urbanization, and the longer the urban-rural inequality will last. This mechanism can potentially explain the lower urbanization rate and higher urban-rural inequality in China under a unified framework.